Cross-Modality Temporal Processing Deficits in Developmental Phonological Dyslexics - Cestnick, Laurie (Brain and cognition, 2001)
Neuroanatomical evidence suggests that poor readers may have abnormal lateral (LGN) and medial (MGN) geniculate nuclei responsible for temporal processing in visual and auditory domains respectively (Livingstone & Galaburda, 1993). Although behavioral evidence does support this neuroanatomical evidence in that poor readers have performed poorly on visual and auditory tasks thought to require the utilization of the LGN and MGN, respectively, appropriate examination of the coexistence of these behavioral abnormalities in the same population of poor readers has yet to take place. The present study examined correlations between visual and auditory temporal processing scores of all readers (collapsed groups), good readers, and poor readers who were isolated into phonological and surface dyslexic subtypes. The same subjects and data from Cestnick and Coltheart (1999) and Cestnick and Jerger (2000) were used to run the analyses. Results demonstrated a multitude of correlations between these tasks for the phonological dyslexic group only. It is contended that cross-modality temporal processing deficits may exist in poor nonlexical (phonological dyslexics) as opposed to poor lexical (surface dyslexics) readers. It is conceivable that phonological dyslexics may also have deficiencies within the LGN and MGN, or perhaps within systems related to these nuclei. The precise cause of these processing patterns and correlations is still unknown.